Linguistic representation of the concept BERLIN WALL in German eonyms - E. E.O. Tumanova (Вестник Самарского университета: История, педагогика, филология, 2024)
The article is devoted to the study of linguistic representation of the concept BERLIN WALL in modern German. The main goal of the article is to identify and describe eonyms (key words of the epoch) that preserve the historical memory of the Berlin Wall in modern German. The material of the study was eonyms selected from the rating lists of the linguistic action of the German Language Society (Gesellschaft für deutsche Sprache e. V.) «Word of the Year» for the period from 1978 to 2020, verbalizing the concept BERLIN WALL. The application of comparative-historical and descriptive methods made it possible to identify eonyms representing the result of linguistic reflection of the most important political phenomenon in modern German history. The article provides a linguocultural analysis of the selected eonyms in synchronic and diachronic aspects. The author describes the influence of the BERLIN WALL concept on the perception of East and West German citizens of each other, analyses the linguistic reflection of changes in political and social life in Germany in the critical era after German reunification. The description of the socio-historical contexts of the emergence of eonyms as representatives of the BERLIN WALL concept allows us to characterise the existing linguistic stereotypes in the German language. The analysis highlights the eonyms and their derivatives, which appear with certain cyclicity, linking historical events with each other and characterising the dynamic development of society and language. The unfolding of the meanings projected in the eonyms allows us to identify the most significant historical events reflected in the concept of BERLIN WALL, to interpret the differences in communicative behaviour between the inhabitants of East and West Germany.